Evolutionary and transcriptional analyses of a pentraxin-like component family involved in the LPS inflammatory response of Ciona robusta. Issue 111 (April 2021) - Vizzini, Aiti; Dumas, Francesca; Di Falco, Felicia; Arizza, Vincenzo
Abstract: Pentraxins (PTXs) are a superfamily of conserved proteins which are components of the humoral arm of innate immunity. They are considered to be functional ancestors of antibodies and are classified into short and long types. In this study, we show that a pentraxin-like component (Ptx-like) with a C-terminal PTX domain, highly homologous to the short PTX of H. sapiens CRP, and a long N-terminal domain typical of long PTXs, is involved in the inflammatory response of Ciona robusta under LPS exposure in vivo . Analyses of protein domains as well as 3D modelling and phylogenetic tree supported the close relationship of Ptx-like with mammalian CRP, suggesting that C. robusta Ptx-like shares a common ancestor in the chordate lineages. qRT-PCR analysis showed that Ptx-like was transcriptionally upregulated during the inflammatory process induced by LPS inoculation and that it is involved in the initial phase as well as the secondary phase of the inflammatory response in which matrix remodelling and the achievement of homeostasis occur. In situ hybridisation assays revealed that gene transcription was upregulated in the pharynx post-LPS challenge in vivo, and that Ptx-like was expressed by clusters of haemocytes, mainly granulocytes, inside the pharynx vessels. We also found transcript-expressing granulocytes flowing in the musculature and in the lacunae of the circulatory system. These data supported that Ptx-like is a potential molecule of the acute-phase response in C. robusta immune defence systems against bacterial infection. Highlights: Genome of Ciona robusta reveals a pentraxine-like gene. Ptx-like of C. robusta shows a C-terminal domain homologous to the H. sapiens CRP. Ptx-like of C. robusta is involved in the LPS inflammatory response. Ptx-like of C. robusta is expressed mainly by granulocytes. Ptx-like is a potential molecule of the acute-phase response in Ciona robusta.